Defining risks of instrumental delivery in a large UK cohort. (18th April 2012) - Wang, J; Vause, S; Tower, C
Abstract : Background: Instrumental delivery accounts for approximately 10-15% of UK deliveries. It is increasingly scrutinised for complication rates, yet there is variable data in the literature describing complication rates in the UK, with, for example, third degree tear rates for forceps deliveries of 8-12% being reported (RCOG 2010). This study sought to describe complication rates in a large UK cohort, which could subsequently be used to generate audit standards. Methods: Data was collected from all instrumental deliveries conducted at a large tertiary referral centre from October 2008- June 2011, using an electronic audit proforma that also served as the medical record. Results: Data was available for 1985 deliveries; 688 (35%) ventouse, 905 (46%) forceps, 178 (9%) kiellands, 51 (2%) rotational ventouse, 163 (8%) 2 instruments. Forceps was associated with an increased risk of third degree tears (p<0.01 Mann-Whitney) of 6.3% compared to 2.6% for ventouse delivery. Forceps were also associated with an increased estimated blood loss (EBL) of median 500mls (interquartile range 300-700mls) compared to 300mls (200-500mls) for ventouse (p<0.01). Babies born using forceps had a higher median birthweight of 3452g (IQR 3100-3835) compared to 3250g (IQR 2948-3600g) for ventouse, (p<0.01, Mann-whitney). Conclusions: This cohort represents one of the largest published UK cohorts of women undergoing instrumental deliveries, and can be used to set audit standards. Forceps is associated with increased blood loss and third degree perineal trauma. However, the risks of the latter were less than those suggested in the RCOG consent advice, suggesting this guidance may require adjustment.